PRE-SERVICE SOCIAL STUDIES TEACHERS' PERCEPTIONS OF EUROPE, THE MIDDLE EAST, AND THE NEIGHBORING COUNTRIES OF TURKEY - (:unkn) unknown (HACETTEPE UNIV, 2010)
Based on qualitative research method, the purpose of this study was to describe and document social studies teacher candidates' perceptions of Europe, the Middle East and Turkey's neighbors together with their perspectives on the cultures of the Middle East and Europe. A purposeful sampling was used to identify and recruit research participants and a semi-structured interview protocol was employed to elicit participants' viewpoints on the research topic. The analysis of the interview transcripts by means of the techniques and strategies of inductive qualitative data analysis showed that participants' viewpoints on the topic were characterized by a dualistic thinking in that they viewed Turkey's neighbors solely in terms of a friend-enemy dichotomy, drawing heavily on their historical knowledge in their explanations which were mainly political in character and focus. Participants' viewpoints were in part affected by their gender.
Keywords: social studies; teacher candidates; pre-service teacher perspectives; approaches to cultures; RELIGION